Synthesis of 6-(Fluoromethyl)-19-norcholest-5(10)-en-3-ol, a Fluorinated Analogue of NP-59, using the Mild Fluorinating Reagent, TBAF(Pinacol)2 - Winton, Wade P.; Brooks, Allen F.; Wong, Ka Kit; Scott, Peter J. H.; Viglianti, Benjamin L. (SynOpen, 2019)
For 45 years, efforts to prepare a fluorinated analogue of the scintiscanning/SPECT agent 6-(iodomethyl)-19-norcholest-5(10)-en-3-ol (NP-59) for development of a PET imaging agent have failed due to undesired elimination reactions and unexpected rearrangements observed while utilizing a wide variety of fluorinating conditions (e.g., cesium fluoride, silver fluoride, (2-chloro-1,1,2-trifluoroethyl)diethylamine (FAR), diethylaminosulfur trifluoride (DAST), and hexafluoropropene diethylamine FPA). Herein, we report the full synthesis of NP-59, followed by the four-step synthesis of 6-(fluoromethyl)-19-norcholest-5(10)-en-3-ol (FNP-59) using a recently developed mild fluorinating reagent, less prone to producing elimination reactions in the preparation of primary fluorides, TBAF(pinacol)2, with an overall yield of 16% (four steps). Also included is an evaluation of the TBAF(pinacol)2 reagent on eight test substrates to investigate its scope.
Keywords: steroids; PET; fluorination; cholesterol; adrenal